Is Helicobacter pylori Infection the Primary Cause of Duodenal Ulceration or a Secondary Factor? A Review of the Evidence. (10th March 2013) - Kate, Vikram; Ananthakrishnan, N.; Tovey, Frank I.
Abstract : Helicobacter pylori ( H. pylori ) has a role in the multifactorial etiology of peptic ulcer disease. A link between H. pylori infection and duodenal ulcer disease is now established. Other contributing factors and their interaction with the organism may initiate the ulcerative process. The fact that eradication of H. pylori infection leads to a long-term cure in the majority of duodenal ulcer patients and the fact that the prevalence of infection is higher in ulcer patients than in the normal population are cogent arguments in favor of it being the primary cause of the ulceration. Against this concept there are issues that need explanation such as the reason why only a minority of infected persons develop duodenal ulceration when infection with H. pylori is widespread. There is evidence that H. pylori infection has been prevalent for several centuries, yet duodenal ulceration became common at the beginning of the twentieth century. The prevalence of duodenal ulceration is not higher in countries with a high prevalence of H. pylori infection. This paper debate puts forth the point of view of two groups of workers in this field whether H. pylori infection is the primary cause of duodenal ulcer disease or a secondary factor.